HIV AND CANCER: ARE THEY RELATED? - Chaterina Janes Pratiwi (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
People living with HIV (PLHIV) are at higher risk of developing various types of cancer and viral infections compared to the general population. Cancers after diagnosis HIV (AIDS-defining cancers) include Kaposi's sarcoma, cervical cancer, and lymphoma. However, cancer can be various types of cancer, it's called non-AIDS defining cancers (NADC). The aim of this study was to identify the relatedness between cancer and HIV and estimate the timeframe for the onset of cancer symptoms after HIV infection. The descriptive analysis method involved 23 respondents with HIV and cancer. The study results showed NADC: breast cancer, liver cancer, leukemia, brain cancer, nasopharyngeal cancer, colon cancer, and rectal cancer. Whereas, HIV-related cancers included cervical cancer and lymphoma. The average time to cancer diagnosis after HIV was 2.73 years, with a standard deviation of 3.06 years, indicating large range of variation in each respondent. The confidence interval of 1.41-4.06 years means a high time difference between respondents. The earliest time to cancer symptoms in HIV was 0.6 years, and the longest time was 14.6 years. Timeframe for cancer to appear after HIV diagnosis is influenced by severe immunodeficiency, as indicated by decreased CD4 counts, age, opportunistic infections, genetic history of cancer, and cancer type. It is important to have self-awareness about early cervical cancer screening for HIV-positive women and regulations that integrate cancer screening services into HIV service units.